Prevalence Of Vitamin A And Vitamin D Deficiency Amongst Children Under Five Years And Women Of Reproductive Age In Madhya Pradesh - Kaur, Supreet (Indian Journal of Community Health, 2015)
Introduction: Vitamin A deficiency (VAD) and vitamin D deficiency (VDD) are major nutritional concern in lower income countries. Staple food fortification is an effective complementary strategy to reduce micronutrient malnutrition at population level. Rationale: The present study was conducted to determine the burden of vitamin A and D deficiencies in Madhya Pradesh prior to the introduction of vitamin A and D fortified vegetable oil in the market. Objectives: To determine the prevalence of VAD and VDD in children under five years of age and women of reproductive age. Methods: A multistage stratified cross-sectional survey was conducted between October-November 2013 in Indore, Gwalior and Betul. Venous blood was available for 577 women of reproductive age and 561 children 6-59 months of age in the urban strata. Serum retinol concentration corrected for inflammation (CRP) <0.70 umol/L and 25-hydroxyvitamin D (25(OH)D) concentration <20 ng/ml were used to define VAD and VDD, respectively. Standard procedure was followed for collection, storage and estimations. Results: VDD was prevalent among 74.6% (n=560) women, mean age of 26.7±3.3 years, and among 52.0% (n=577) of children (2.9 ± 1.3 years). It was estimated that, 16.9% (n=561) of women and 13.4% (n=574) of children had sub-clinical VAD. The prevalence of VDD among children in Gwalior and Betul was lower (43-49%) compared to Indore (64%) (p=0.000); but these district-wise VDD differences were not apparent among women in Indore (78%), Gwalior (78%), and Betul (71%). In contrast, VAD was substantially lower among women (8%) and children (3%) in Betul compared to Gwalior (18% of women; 21% of children) and Indore (25% of women and 19% of children) (p=0.000). Conclusion: Prevalence of both VAD and VDD in Madhya Pradesh is high, marking it as major public health problem. Increased coverage of micronutrient fortified foods at the population level will be an important strategy to mitigate the burden of micronutrient deficiencies.